The Novel Enterococcus Phage vB_EfaS_HEf13 Has Broad Lytic Activity Against Clinical Isolates of Enterococcus faecalis - Lee, Dongwook; Im, Jintaek; Na, Hongjun; Ryu, Sangryeol; Yun, Cheol-Heui; Han, Seung Hyun (Frontiers in Microbiology, 2019)
Enterococcus faecalis is a Gram-positive, facultative anaerobic bacterium frequently found in the gastrointestinal tract, oral cavity, and periodontal tissue. Although it is considered a commensal, it can cause bacteremia, endocarditis, endodontic infections, and urinary tract infections. Because antibiotics are cytotoxic not only to pathogens, but also to health-beneficial commensals, phage therapy has emerged as an alternative strategy to specifically control pathogenic bacteria with minimal damage to the normal flora. In this study, we isolated a novel phage, Enterococcus phage vB_EfaS_HEf13 (phage HEf13), with broad lytic activity against 12 strains of E. faecalis among the three laboratory strains and 14 clinical isolates of E. faecalis evaluated. Transmission electron microscopy showed that phage HEf13 has morphological characteristics of the family Siphoviridae. Phage HEf13 was stable at a wide range of temperature (4–60°C) and showed tolerance to acid or alkaline (pH 3–12) growth conditions. Phage HEf13 had a short latent period (25 min) as well as a large burst size (352 virions per infected cell). The lytic activity of phage HEf13 at various multiplicities of infection consistently inhibited the growth of diverse clinical isolates of E. faecalis without any lysogenic process. Moreover, phage HEf13 showed an effective lytic activity against E. faecalis on human dentin ex vivo infection model. Whole genome analysis demonstrated that the phage HEf13 genome contains 57,811 bp of double-stranded DNA with a GC content of 40.1% and 95 predicted open reading frames (ORFs). Annotated functional ORFs were mainly classified into four groups: DNA replication/packaging/regulation, phage structure, host cell lysis, and additional functions such as RNA transcription. Comparative genomic analysis demonstrated that phage HEf13 is a novel phage that belongs to the Sap6virus lineage. Furthermore, the results of multiple sequence alignment showed that polymorphism of PIPEF contributes to determine the host specificity of phage HEf13 against various E. faecalis strains. Collectively, these results suggest that phage HEf13 has characteristics of a lytic phage, and is a potential therapeutic agent for treatment or prevention of E. faecalis-associated infectious diseases.